2020
DOI: 10.1088/1361-648x/ab74e4
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of the local moment molecular spin transistor

Abstract: Local moment molecular systems have now been used as the conduction channel in gated spintronics devices, and some of these three terminal devices might even be considered molecular spin transistors. In these systems, the gate voltage can be used to tune the molecular level alignment, while applied magnetic fields have an influence on the spin state, altering the magnetic properties, and providing insights to the magnetic anisotropy. More recently, the use of molecular spin crossover complexes, as the conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…The successes with organic electronics, combined with indications of success in addressing the complex grand challenge of manipulating magnetically ordered states by electrical means, suggest new approaches and applications to develop novel spintronics. In molecular systems, the spin crossover (SCO) relates to the transition between a low spin (LS) of the metal ion (indeed, diamagnetic state in the case of the Fe 2+ system) to a high-spin (HS) paramagnetic state in 3D transition metal compounds, and for quite some time now, it has been suggested that the spin crossover (SCO) phenomenon has potential applicability in molecular spintronic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In such device elements, based on the molecular spin state, is very likely that state switching may be accomplished without large current densities or power consumption.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The successes with organic electronics, combined with indications of success in addressing the complex grand challenge of manipulating magnetically ordered states by electrical means, suggest new approaches and applications to develop novel spintronics. In molecular systems, the spin crossover (SCO) relates to the transition between a low spin (LS) of the metal ion (indeed, diamagnetic state in the case of the Fe 2+ system) to a high-spin (HS) paramagnetic state in 3D transition metal compounds, and for quite some time now, it has been suggested that the spin crossover (SCO) phenomenon has potential applicability in molecular spintronic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In such device elements, based on the molecular spin state, is very likely that state switching may be accomplished without large current densities or power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Such devices work where the voltage control of the molecular spin states leads to nonvolatile conductance changes [13,14]. From these many perspectives of memory devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14] made possible by the molecular spinstate transition, we can construct a list of some of the key elements needed to make a competitive nonvolatile molecular device for memory applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,5,6,[8][9][10][11][12][13][14][15][16][17]22,23 Bistability is an essential ingredient for implementing a spin crossover complex into a molecular device. 24 For a successful realization of such devices, it is important to investigate the impact of different characterization methods on the spin crossover properties of promising candidates. In this regard, the spin crossover coordination polymer [Fe(L1)(bipy)] n (where L1 is a N 2 O 2 2− coordinating Schiff base-like ligand bearing a phenazine fluorophore and bipy = 4,4′-bipyridine), of Figure 1a, is particularly interesting.…”
Section: Introductionmentioning
confidence: 99%